PENGARUH BEHAVIORAL FINANCE TERHADAP KEPUTUSAN BERWIRAUSAHA PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS ABDURACHMAN SALEH SITUBONDO - Dwi Perwitasari Wiryaningtyas; Riska Ayu Pramesthi (Relawan Jurnal Indonesia, 2018)
This study aims to study the direct and indirect interactions of financial behavior, namely, demographic factors (X1) and psychological factors (X2), on entrepreneurial decisions (Y). Successful research outputs are research on knowledge about entrepreneurship, publishing new business opportunities for students themselves, for the surrounding community, needing funding from students and the community, and opening new jobs in the community. The population in this study were students of the Faculty of Economics, Abdurachman Saleh University Situbondo who won 983 students. This research uses purposive sampling technique that is sampling with criteria. Determination of the number of samples of respondents using Slovin formula, which amounted to 71 respondents. The method used is the survey method with the type of research explanation or explanation of the research. The data analysis technique used is multiple regression analysis. Demographic Factor Variable (X1) towards Entrepreneurial Decision (Y) based on t test can be associated with the significance of the demographic factor <α that is 0.010 <0.05. It means partially the demographic factor variable (X1) has a significant influence on entrepreneurial decisions (Y). While the influence of Psychological Factor Variables (X2) on entrepreneurial decisions (Y) that the significance value of the psychological factor variable <α is 0,000 <0.05. It means partially the psychological factor variable (X2) has a significant influence on entrepreneurial decisions (Y). Proving, proving the hypothesis that positions the hypothetical factor on entrepreneurial decisions in students of the Faculty of Economics, Abdurachman Saleh University Situbondo is proven true. From the results of the F test for Test F smaller than 0.05 (0,000 <0,05), then the demographic factors and psychological factors simultaneously have a significant effect on entrepreneurial decisions. Demographic factors and psychological factors that can affect the students of the Faculty of Economics, Abdurachman Saleh University Situbondo.